Utilizacion de ramio (Boehmeria nívea) como alternativa de alimentación en un sistema de produccion lechero de bajura en San Carlos, Costa Rica - Rojas-Ugalde, Adolfo (Instituto Tecnológico de Costa Rica, 2019)
In the present study, the effect of the grain substitution by ramie in the dairy cows diets of the specialized production system of milk performance and the quality performance (concentration of fat, protein, lactose and total solids) was evaluated. There are also evaluated the variables of milk urea nitrogen (MUN), the content of somatic cells and also the economic component of each diet to determine how this impacts on the profitability of the production system. This investigation was carried out in the Huetar Norte Region, in Hacienda el Hule, located in San Juan de Florencia downtown, San Carlos, Costa Rica. A total of three treatments were evaluated. The control treatment, treatment two, with 10% substitution of grain by ramie in dry matter and treatment three, with 20% substitution of grain by ramie in dry matter. The experimental design corresponds to a cross over Latin rectangle 3x3 repeated twice. For this experiment was used six cows with similar productive characteristics in their first third of lactation. In the frist group all the treatments were applied in different evaluation periods, during a period of one week of adaptation to the diet and another week of data collection; The second group the animals were fed following the same instruction. The statistical analysis showed no significant differences (P> 0.05) for any of the variables studied. It was also found that the most profitable diets were those that had a greater inclusion of ramie in them. It has concluded that the use of ramie as sustitution up to 20 % of grain does not alter the components of production performance or quality performance of milk, but it make them more profitable up to 15.38%.
Tesis (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de Costa Rica, Escuela de Agronomía, 2019.
Keywords: Producción lechera; Costos de producción; Bovinos; Nutrientes; Leche; Pasturas; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING